Electrochemical study of fuming sulphuric acids : I. Kinetic parameters of the anodic and cathodic reactions on platinum electrodes - Garrera, H. A. (1968)
Kinetic parameters related to the anodic and cathodic processes in the electrolysis of fuming sulphuric acids on bright platinum and platinized platinum electrodes have been established, the electrolyte being kept at rest. Experiments cover temperatures from 25 to 70°C and oleums with a sulphur trioxide concentration from about 5 to 28 per cent. The yields of the different anodic and cathodic products mentioned in a previous publication have been confirmed and results for others are given. The anodic reaction is characterized by current/voltage curves which fit Tafel plots at high voltage, with a slope close to 2·3(2RT/F). The cathodic current/voltage curves plotted according to the Tafel equation exhibit three different regions. (i) At voltages lower than 0·4 V, a Tafel line with a slope of 2·3(RT/F) is observed. (ii) At about 0·5 V a limiting current is shown. These regions are related to the reduction of sulphur trioxide. (iii) At voltages larger than 0·7 V, a clear Tafel line region appears again, involving a 2·3 (2RT/F) slope. The latter is related to the evolution of hydrogen and the simultaneous presence of a blue tinge in the oleums, which is attributed to the formation of disulphur trioxide.